RESEARCH OF TECHNOLOGIES FOR RESTORATION OF PARTS OF AGRICULTURAL EQUIPMENT HYDROSYSTEMS - Іванкова, Олена; Чумак, Марина; Федін, Віталій (SWorldJournal, 2025)
There is no agricultural machinery that could work forever. In the process of operation, sooner or later the question of repair, purchase of spare parts arises.The task of technical service is to optimally solve such issues. And, at the same time, in the